Effects of Directionality on Interpreting Performance: Evidence From Interpreting Between Chinese and English by Trainee Interpreters - Chou, Isabelle; Liu, Kanglong; Zhao, Nan (Frontiers in Psychology, 2021)
Interpreters can either interpret from the first language (L1) to the second language (L2), or in the other direction. Understanding translation and interpreting as a direction-dependent process contributes to a wider and more critical view regarding the role of both languages in the process, as well as the identity, perspectives, and preferences of translators. The effect of directionality primarily weighs on stimulus and individual factors. This study explores the impact of directionality on the performance of trainee interpreters by examining four critical aspects of quality in target speeches, namely: speech rate, information completeness, delivery, and quality of expression. We observed an advantage for L2-L1 over L1-L2 interpreting in the form of interpreting quality (i.e., delivery and quality of expression) but not in content (i.e., the level of information retained in the target language). These effects of interpreting directionality suggest an important role of L2 proficiency in interpreting. Moreover, L1-L2 interpreting is cognitively demanding compared to L2-L1 interpreting for trainee interpreters. This research sheds light on the cognitive mechanisms of interpreting in different directions and provides pedagogical recommendations for training interpreters.